The governator : from muscle beach to his quest for the White House, the improbable rise of Arnold Schwarzenegger - Halperin, Ian (William Morrow, 2010)
Reveals the untold story of Arnold Schwarzenegger, chronicling his journey from Mr. Universe bodybuilder to Hollywood hit-maker to governor of California.